2005
DOI: 10.1074/jbc.m413441200
|View full text |Cite
|
Sign up to set email alerts
|

The AGAAAAGA Palindrome in PrP Is Required to Generate a Productive PrPSc-PrPC Complex That Leads to Prion Propagation

Abstract: The molecular hallmark of prion disease is the conversion of normal prion protein (PrP C ) to an insoluble, proteinase K-resistant, pathogenic isoform (PrP Sc ). Once generated, PrP Sc propagates by complexing with, and transferring its pathogenic conformation onto, PrP C . Defining the specific nature of this PrP Sc -PrP C interaction is critical to understanding prion genesis. To begin to approach this question, we employed a prion-infected neuroblastoma cell line (ScN2a) combined with a heterologous yeast e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
96
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 29 publications
2
96
0
Order By: Relevance
“…The hydrophobic region of PrP, stretching from residues 111 to 133 in mouse PrP, may play a role in modulating prion toxicity and infectivity; synthetic peptides of this region interfere with prion propagation in vitro (4), whereas large deletions of this region prevent formation of protease-resistant PrP in cell culture models (5). The hydrophobic region is believed to undergo significant structural change following prion infection, as antibodies directed toward PrP(90 -120) can detect PrP C but not PrP Sc (6).…”
mentioning
confidence: 99%
“…The hydrophobic region of PrP, stretching from residues 111 to 133 in mouse PrP, may play a role in modulating prion toxicity and infectivity; synthetic peptides of this region interfere with prion propagation in vitro (4), whereas large deletions of this region prevent formation of protease-resistant PrP in cell culture models (5). The hydrophobic region is believed to undergo significant structural change following prion infection, as antibodies directed toward PrP(90 -120) can detect PrP C but not PrP Sc (6).…”
mentioning
confidence: 99%
“…Lampo et al (2007) , that it modulates the formation of transmembrane PrP isoforms (Hegde et al, 1998) and that it is important for basolateral sorting of PrP in a cell (Uelhoff et al, 2005). Furthermore, the AGAAAAGA palindrome may play a part in the diseasespecific PrP Sc -PrP C interaction (Norstrom & Mastrianni, 2005): peptides containing this sequence are neurotoxic (Forloni et al, 1993) and amyloidogenic (Gasset et al, 1992), and the variant AGAAVAGA is linked to Gerstmann-Sträussler-Scheinker syndrome, a genetic form of human prion disease (Mallucci et al, 1999). The homology in this region between PrP and Sho implies that there is similar cellular sorting and ligands and that they use similar mechanisms to promote their neuroprotective properties .…”
mentioning
confidence: 99%
“…between normal PrP and its disease-specific isoform PrP Sc (Norstrom & Mastrianni, 2005). Whether the three ovine Sho variants with the sequences AGAAAGA, AGAAAAGA or AGAAAAAGA can all compete with or substitute PrP in these interactions remains an important question for future studies.…”
mentioning
confidence: 99%
“…25−27 Conversely, PrP molecules that are deleted in the hydrophobic region have greater conformational stability than WT (wild-type) PrP 28 and are refractory to PrP Sc -induced conversion. 29,30 From the antibodies used in this research, only Pri 308 has been reported to block Prp oligomer toxicity, 31 but in our case this antibody could not detect Prp mimics. One common problem with amyloid oligomers is that they are unstable and disappear as mature fibrils and amorphous aggregates in solution; our results clearly show a preparation that represents a stable oligomeric transitional aggregation state that is not recognized by any sequence dependent antibody.…”
mentioning
confidence: 63%